The Relationship between Psychoacoustic and Electrophysiological Assessments of Temporal Resolution - Heydari, Kamran; Tahaei, Ali Akbar; Pourbakht, Akram; Haghani, Hamid; Nazeri, Ahmadreza (Journal of the American Academy of Audiology, 2021)
Background Temporal resolution is essential to speech acoustic perception. However, it may alter in individuals with auditory disorders, impairing the development of spoken and written language. The envelope of speech signals contains amplitude modulation (AM) that has critical information. Any problem reducing the listener's sensitivity to these amplitude variations (auditory temporal acuity) is likely to cause speech comprehension problems. The modulation detection threshold (MDT) test is a measure for evaluating temporal resolution. However, this test cannot be used for patients with poor cooperation; therefore, objective evaluation of MDT is essential.Purpose The main aim of this study is to find the association between the auditory steady-state response (ASSR) and psychoacoustic measurement of MDT at different intensity levels and to assess the amplitude and phase of ASSR as a function of modulation depth.Design This was a correlational research.Study Sample Eighteen individuals (nine males and nine females) with normal hearing sensitivity, aged between 18 and 23 years, participated in this study.Data Collection and Analysis ASSR was recorded at fixed AM rates and variable AM depths for carrier frequencies of 1,000 and 2,000 Hz with varying intensities. The least AM depth, efficient to evoke an ASSR response, was interpreted as the physiological detection threshold of AM. The ASSR amplitude and phase, as a function of AM depth, were also evaluated at an intensity level of 60 dB hearing level (HL) with modulation rates of 40 and 100 Hz. Moreover, the Natus instrument (Biologic Systems) was used for the electrophysiological measurements. An AC40 clinical audiometer (Intra-acoustic, Denmark) was also used for the psychoacoustic measurement of MDT in a similar setting to ASSR, using the two-alternative forced choice method. Pearson's correlation test and linear regression model and paired t-test were used for statistical analyses.Results A significant positive correlation was found between psychoacoustic and electrophysiological measurements at a carrier frequency of 1000 Hz, with a modulation rate of 40 Hz at intensity levels of 60 dB HL (r = 0.63, p = 0.004), 50 dB HL (r = 0.52, p = 0.02). A significant positive correlation was also found at a carrier frequency of 2000 Hz, with a modulation rate of 47 Hz at 60 dB HL (r = 0.55, p = 0.01) and 50 dB HL (r = 0.67, p = 0.002) and a modulation rate of 97 Hz at 60 dB HL (r = 0.65, p = 0.003). Moreover, a significant association was found between the modulation depth and ASSR amplitude and phase increment at carrier frequencies of 1,000 and 2000 Hz, with modulation rates of 40 and 100 Hz.Conclusion There was a significant correlation between ASSR and behavioral measurement of MDT, even at low intensities with low modulation rates of 40 and 47 Hz. The ASSR amplitude and phase increment was a function of modulation depth increase. The findings of this study can be used as a basis for evaluating the relationship between two approaches in the clinical population.
Keywords: psychoacoustic; electrophysiological; temporal resolution; ASSR; MDT